Pengaruh Penggunaan Modul Digital Terhadap Hasil Belajar Kognitif Peserta Didik Pada Pembelajaran Pendidikan Agama Islam Di Kelas XI IPA 1 SMAN 14 Garut - Maria, Anly; Fatonah, Imas (STAI Al-Musaddadiyah Garut, 2023)
Cognitive learning outcomes are the results students achieve through learning processes that involve techniques such as memorization and retention, allowing them to master foundational knowledge or understand other concepts. To date, students' cognitive learning outcomes in Islamic Religious Education (PAI) have not developed satisfactorily. Issues include difficulties in understanding the material, inability to explain the concepts taught, and challenges in retaining information. Digital modules engage students actively in the learning process, potentially enhancing their cognitive learning outcomes. This study aims to describe the impact of using digital modules on students' cognitive learning outcomes in PAI instruction. The objective is to assess the relationship between the use of digital modules and the improvement of students' cognitive learning outcomes. The research method employed is descriptive quantitative correlational. Data collection techniques include observation, questionnaires distributed to 35 respondents, and documentation studies. Data processing is conducted through statistical data analysis. The findings of this research reveal that the use of digital modules in learning received an average rating of 4.26, categorized as very good. Additionally, the improvement in students' cognitive learning outcomes in PAI instruction achieved an average rating of 4.32, also categorized as very good. Statistical tests indicate that the use of digital modules accounts for 62.12% of the variation in students' cognitive learning outcomes, aligning with the goals and functions of Islamic Religious Education. The remaining 37.88% is influenced by other factors not examined in this study. Keywords: Digital Modules, Cognitive Learning Outcomes, Islamic Religious Education Instruction.